Fermentation With Pleurotus Ostreatus Enhances the Prebiotic Properties of Germinated Riceberry Rice - Soodpakdee, Kanjana; Nacha, Jutamat; Rattanachart, Nattapol; Owatworakit, Amorn; Chamyuang, Sunita (Frontiers in Nutrition, 2022)
Rice is the staple food for more than half of the world's population. In recent years, awareness of the health benefits of colored rice varieties and germinated rice has gradually increased. Riceberry rice (R), a black-purple variety, was germinated and subsequently fermented with Pleurotus ostreatus mycelium (M) to improve nutrient quality and prebiotic properties. The γ-aminobutyric acid (GABA) and β-glucan contents were measured daily for a total of 4 days. The prebiotic activities of R, germinated Riceberry rice (GR), and germinated Riceberry rice with mycelium (GRM) were evaluated on the probiotic bacteria Pediococcus sp., Lactobacillus acidophilus, and Streptococcus lactis. Results were compared with the M treatment and with the commercial prebiotic agents: inulin and β-glucan. The treatments were also used to evaluate growth of the pathogen Escherichia coli. The GABA content peaked after 3 days of germination. The GR sample fermented with M for 3 days had the optimal concentration of both β-glucan and GABA. Evaluation of the prebiotic properties of rice samples and the commercial standards (inulin and β-glucan) showed that these were enhanced on the GR and GRM treatments. Results also showed the improvement of prebiotic properties on GR as the R sample did not show any prebiotic properties in all probiotic bacteria, whereas the GR sample showed moderate prebiotic activity score of 0.40, 0.88, and 0.56 on Pediococcus sp., L. acidophilus, and S. lactis, respectively. Furthermore, the prebiotic activity of GR was improved when fermented with M. For further applications, the GRM could be used on rice-based products, such as rice flour, rice crackers, or other rice products to enhance nutritional value and improve digestive system health, especially in the elderly.